Pengaruh Pembelajaran Berbasis Masalah Terhadap Kemampuan Komunikasi Matematis Siswa SMA - mikrayanti mikrayanti (Program Studi Pendidikan Matematika, 2021)
This study aims to obtain an overview of the effect of learning mathematics using a problem-based learning approach on the mathematical communication skills of class XI science students at a school in Bima district. This research is a quasi-experimental research with the research design used is Posttest Only Control Design. The population in this study were all high school students of class XI science in one of the SMA Regency of Bima, totaling 199 people spread over 6 science classes. The sample used in this study only took two classes, namely the experimental class and the control class, with cluster random sampling technique sampling. The instruments used in this study were test and non-test instruments. The test instrument is in the form of a test in the form of a description to measure students' mathematical communication skills. The results showed that the problem-based learning model had an effect on the mathematical communication skills of class XI science students at one of the senior high schools in the bima district.